Les ardoises gravées de l’abbaye de Prémontré (Aisne), un support de notation musicale aux xve-xvie siècles - Galmiche, Thierry; Buccio, Vincent (Archéologie médiévale, 2016)
L’abbaye de Prémontré a été fondée en 1121 dans l’évêché de Laon. Trois ardoises gravées de notations musicales ont été mises au jour lors de fouilles archéologiques réalisées dans l’enceinte abbatiale entre 2010 et 2012. Pour deux d’entre elles, ces inscriptions consistent uniquement en des portées. Pour l’autre ardoise, des notes de musique ont, en outre, été dessinées.Un premier recensement indique que ce type d’artefact n’est pas isolé, trente-trois objets similaires ont en effet été dénombrés. Ils sont tous datés des xve-xve siècle. Dans l’état actuel des recherches, l’aire géographique de ces découvertes s’étend du sud-ouest de la France aux îles Britanniques en passant par la Bretagne, l’Île-de-France, la Picardie, la Belgique et les Pays-Bas.L’essentiel de ces ardoises ont été retrouvées en contexte ecclésiastique. Leur examen fait ressortir des disparités tant au niveau de la forme des ardoises que des dimensions, parfois difficiles à apprécier, et des inscriptions qui y sont portées. A minima, des portées sont présentes (à l’exception de l’exemplaire de la chapelle de Lopikerkapel, les notes sont en notation blanche mesurée). Dans d’autres cas, l’intention de réaliser des supports destinés à être réutilisés est patente.Ces différences nous ont conduits à définir trois catégories d’ardoise. Les premières, sur lesquelles sont inscrites des portées et, de façon occasionnelle des notes, ont été utilisées comme simple support à noter de la musique. Après chaque usage, elles sont effacées. Ces supports ont ainsi pu servir pour l’apprentissage de la composition ou pour l’entraînement à la concordance des voix. Les ardoises 2 et 3 de Prémontré ont été rangées dans ce groupe. Des extraits musicaux sont intentionnellement gravés sur les schistes de la deuxième catégorie mais leur usage est unique. L’emploi de ces ardoises comme support temporaire de composition peut être proposé. Une fois l’extrait recopié, l’ardoise est jetée. La troisième catégorie, numériquement moins importante, est constituée d’ardoises à usages répétés. Ces schistes pourraient avoir été utilisés dans l’apprentissage par mémorisation ou comme supports pour des choristes. L’exemplaire 1 de Prémontré, classé dans cette catégorie, est le plus complet : il est exceptionnel par son état de conservation et par la longueur du fragment musical gravé. Chacune de ces ardoises pourrait donc avoir été utilisée dans la composition ou l’apprentissage de la musique.
Keywords: prémontré; 🎶 musicology

The Cartulary of the Abbey of Prémontré: A Story of Conflict and Resolution - Wacha, Heather (Essays in Medieval Studies, 2016)
In lieu of an abstract, here is a brief excerpt of the content: The Cartulary of the Abbey of Prémontré: A Story of Conflict and Resolution Heather Wacha Introduction Monastic cartularies offer important evidence for the study of an institution’s social and economic history. Compiled of papal bulls, privileges, donations, confirmations, and property transactions, the textual evidence found in cartulary charters can narrate the growth and decline of an abbey’s revenues and rights over the course of decades. It can also recount the stability and fluidity of social relationships with lay patrons, other religious institutions, and dependent houses. In addition to charter content, the process of selecting and organizing charters for cartulary construction provides further insights into a religious institution’s historical context.1 For the cartulary of the Abbey Saint-Jean Baptiste de Prémontré, located in the region of Picardy, France, the textual and codicological evidence together tell a story of how two long-term conflicts and the abbey’s desire to memorialize their resolution resulted in the completion of its cartulary in 1239. At present there exists no critical edition of the Abbey of Prémontré’s cartulary. In 1975, the Centre d’études et de recherches prémontrées (CERP) launched a cartulary edition project based on the original manuscript, Soissons, Bibliothèque municipale (henceforth Bm), MS. 7. By 1988, Françoise Muret had finished the transcriptions of all cartulary acts, found today at the Institut de recherche d’histoire des textes (henceforth IRHT) in Orléans and Paris, yet her substantial work and significant contributions remain unpublished.2 The cartulary’s notice, also held at the IRHT, posits a range of dates for the completion of the abbey’s cartulary between 1239 and 1250, but no follow-up studies have narrowed this window. This article argues that the cartulary was completed no later than 1239 and that this date was not an arbitrary one. The origins of the Abbey of Saint-Jean Baptiste de Prémontré, the founding abbey of the eponymous order, date from 1121, when Norbert of Xantan [End Page 125] (c. 1080–1134) established his houses of religious brothers and sisters at the confluence of three rivers northeast of Paris and west of Laon.3 When Norbert of Xantan left Prémontré in 1126 to become archbishop at Magdeburg, Germany, the abbey continued to flourish under the leadership of Hugh of Fosses (1126–1164), who codified the order’s statutes and liturgy.4 Much of the scholarship addressing the twelfth-and thirteenth-century history of the Abbey of Prémontré has focused on Norbert of Xantan and his spiritual vision for the order as a whole.5 As a result, the abbey’s early history is often portrayed as a time of rapid growth for the order, casting Prémontré as the central force that held the houses and order together.6 Prémontré’s cartulary, however, reveals a moment in the abbey’s history in which tension and conflict were rife, to such a degree that the desire to reinstate a sense of peace and order influenced the process of cartulary construction, as well as the date of completion. While the Abbey of Prémontré is widely accepted and respected as the mother abbey of the Premonstratensian order today, in the thirteenth century challenges from its houses in Germany suggest that this status had yet to be firmly secured. In 1234, Pope Gregory IX drew attention to what had become a general lack of consistent practice across houses within the Premonstratensian order. Within his more global agenda of reform, the pope specifically called for the rewriting of the Premonstratensian statutes, requesting that the abbot-general reconsider the central governing structure of the order, the governing of individual abbeys, and the uniformity of customs and liturgy.7 In essence, the pope sought universal agreement within the order as to who was in charge and what it meant to be a member of the Premonstratensian order. As part of the response to the Pope’s call for reform, Abbot Conrad (1220–1233) and his secretary/librarian, later Abbot Hugh III (1238–1242), initiated Prémontré’s cartulary. Although cartulary construction began in earnest sometime shortly before or around 1234, the settlement of the...
Keywords: prémontré

Norbert von Xanten, die Gründung von Prémontré und die Entstehung des Prämonstratenserordens - Felten, Franz J. (Norbert von Xanten und der Orden der Prämonstratenser : Sammelband zur historischen Vortragsreihe im Norbertjahr 2009/2010 in Magdeburg, 2010)
Keywords: prémontré; 👤 norbert of xanten